Pemanfaatan Novel Sejarah Sebagai Media Pembelajaran Sejarah di Sekolah Menengah Atas - Haris Firmansyah (Peneliti.net, 2023)
This study aims to find out how to use historical novels as a medium for learning history. The research method that researchers use is descriptive qualitative method. This research was conducted at SMK Cahaya Bangsa in Rasau Jaya, Kubu Raya Regency. The techniques used for data collection are observation, interviews, and documentation. Sources of informants in this study were history teachers and class XI students. The results of this study indicate that history teachers have utilized historical novels as learning media. As one of the learning media that can develop and explain imaginative literacy, so that it can help students' interest in studying history. The teacher has a very important role in learning. Like preparing learning media for historical novels. Before starting the lesson , the teacher prepares a lesson plan in advance, including the use of historical novels as a learning medium. In its implementation the teacher divides into several groups and gives each group of students a historical novel that is appropriate to the learning material. At the learning evaluation stage the teacher gives assignments to each group to analyze what is contained in the historical novel and asks each group to present their presentation results.